Integrating Modern Technology with Islamic Jurisprudence: The Role of Elsimil in Enhancing Family Resilience through Sadd Dzariah Perspective - Ahmad, Wildanil Musthafa; Syafi, Imam; Hariati, Nina Agus (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2024)
This research focuses on implementing Elsimil to increase family resilience and prevent stunting in children. This research uses library research methods. Primary data includes works such as